Issues Surrounding Socio-Economic Development in the Local Government Areas in Nigeria: A Focus on Financial Budgeting - Edih University Ovuokeroye (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
Developing nations are in dire need for socio-economic growth and development and this desired growth is determined by the economic structure, the political economy and the amount of strategic development plan with purposeful resolve of the National, State and Local governments. More so, development being a long-term, medium-term and sufficiently complemented by short-term plan/ or financial budgeting is paramount to the socio-economic advancement of every nation. Hence, the study examines issues surrounding socio-economic development in local government areas in Nigeria . It is the focus of this study to critically dissect the pivotal role of budgets in local government administration as a socio-economic development strategy of the Nigerian State. The lack of political will and lopsided political structure were found as explanations for the lack of socio-economic development at the local government level. Nigeria, being an independent country is standing on tripod government structure which necessitates the need for the federal, state and local governments to harness resources and efforts to restructure as well as diversify the Nigerian economy. The study also recommends that, local governments should enjoy financial autonomy to enable them participate in building the economy through the initiation and execution of developmental programmes for the local population.